A Critical Analysis of the Bugis Wedding Tradition 'Passampo Siri - Jamal, Ridwan; Mitra, Asandi (Al-Mujtahid: Journal of Islamic Family Law, 2024)
This paper examines the Passampo siri’ tradition (marriage of disgrace) in the Bugis community through paradigmatic analysis using the framework of Critical Theory. The research method used is a literature study to collect data from relevant literature sources. The data were analyzed qualitatively with a paradigmatic approach to achieve contextual and in-depth meaning related to the philosophical background of Passampo Siri’ and its implications for his abolition discourse. The results of the analysis show that Passampo siri’ is actually a socio-cultural entity born from the habitus of the Bugis people towards the concept of self-esteem (siri') as a core value. Removing them without a contextual understanding can threaten the integrity of the values that have been upheld and closely guarded so far. Therefore, this case reminds us of the importance of reflective attitudes and multidimensional analysis before deciding to "break" a tradition that is considered purely irrational. This research seeks to integrate epistemological reflections from critical theory in understanding the Passampo siri’, highlighting how power structures, ideologies, and social norms shape and influence those cultural practices. This study emphasizes that the abolition discourse must consider the historical and social context behind this tradition. The results of this study provide insight that cultural reform requires an approach that respects the complexity and richness of local values, while opening up a space for constructive critical dialogue.